Distortions In the Flux Distribution In Two Dimensional Geometries - Sağlam, Semiha (İstanbul Kültür Üniversitesi Yayınları, 2004)
The subject of this study is distortions of flux distributions observed in Discrete Ordinates Method. To observe these distortions an important two dimensional transport code has been chosen and executed for a wellknolwn test problem. The distributions of scalar flux have been examined by using standard Gauss quadratures for integraJ terms appearing in the source term. Then, the results have been compared with the other transport code and the ray-effect problem has been discussed in detail.

Bu çalışmanın konusu, kesikli Ordinatlar Metodunda gözlenen akı dağılımındaki bozulmalardır. Bu bozulmaları gözlemek üzere iki boyutlu önemli bir transport kodu seçilmiş ve iyi bilinen bir test problemi için koşulmuştur. Skaler akı bozulmaları, kaynak teriminde ortaya çıkan integral terimi yerine standart Gauss quadratür yaklaşımı kullanılarak incelenmiştir. Sonra, sonuçlar bir başka transport kodu ile karşılaştırılmış ve etkisi problemi ayrıntılı olarak tartışılmıştır.
Keywords: discrete ordinate method; ray-effect distortions; gauss-legendre quadrature; ayrık ordinat yöntemi; ray-etkisi çarpıtmalar